1984
DOI: 10.1073/pnas.81.2.560
|View full text |Cite
|
Sign up to set email alerts
|

Neutron-capture therapy of human cancer: in vivo results on tumor localization of boron-10-labeled antibodies to carcinoembryonic antigen in the GW-39 tumor model system.

Abstract: Neutron-capture therapy of human cancer: In vivo results on tumor localization of boron-10-labeled antibodies to carcinoembryonic antigen in the GW-39 tumor model system (immunoreactivity/p-[1,2-dicarba-closo-[1-3H]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 13 publications
(10 reference statements)
1
19
0
Order By: Relevance
“…NMR (CDClg): 7.73 (d, 2 H, Ar-H), 7.32 (d, 2 H, Ar-H), 3.99 (t, 2 H, CH2), 2.41 (s, 3 H, tosyl CH3), 2.16 (m, 2 H, CH2), 1.92 (s, 3 H, carboranyl CHa), 1.88 (m, 2 H, CH2). "B NMR (CH2C12): -4.78, -6.24, -9.46, -10.12, -11.03.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…NMR (CDClg): 7.73 (d, 2 H, Ar-H), 7.32 (d, 2 H, Ar-H), 3.99 (t, 2 H, CH2), 2.41 (s, 3 H, tosyl CH3), 2.16 (m, 2 H, CH2), 1.92 (s, 3 H, carboranyl CHa), 1.88 (m, 2 H, CH2). "B NMR (CH2C12): -4.78, -6.24, -9.46, -10.12, -11.03.…”
Section: Methodsmentioning
confidence: 99%
“…The problem associated with this form of therapy has been the lack of a viable method for the selective delivery of the required quantity of boron-10 to the neoplasm µg/g tumor). Since a number of studies have previously revealed the limitations associated with attaching large numbers of small boron-containing molecules to the antibody (2)(3)(4), attention has recently focused upon the covalent linkage of boron-loaded polymers to the antibody. These methods include the use of boron-labeled poly-DLlysine (5-10), a carborane-linked dextran moiety (oxidized for antibody coupling) (11)(12)(13), and boron-labeled poly-L-ornithine (14).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the 'OB-conjugated antibody on tumour cell growth in BNCT was reported first by Mizusawa et al (1982), Goldenberg et al (1984. They conjugated 50 boron atoms directly to an antibody molecule, but the antibody did not work efficiently in BNCT.…”
Section: Discussionmentioning
confidence: 99%
“…In this approach of cancer treatment, clearly it is decisive to make sure that the boron-loaded molecules invade massively the malignant cells without practically penetrating into the healthy ones. Labelling the boron-loaded compound with a radioactive isotope and determining the distribution of the radioactivity in vivo may be used to evaluate the efficacy of this compound for localizing selectively in the tumour cells [63]. As an alternative, it is also possible (especially when studying model systems) to prepare cell samples or histological sections of a tissue area of interest and examine the relative distribution of 10 B between tumour and healthy cells by NCR.…”
Section: Ncr For Bnctmentioning
confidence: 99%